Peningkatan Kemampuan Literasi Numerasi Siswa melalui Program Kampus Mengajar di SDN 1 Monggas - Saputra, Ari; Zohrani, Zohrani (Al-DYAS, 2022)
Kampus Merdeka Program (MBKM) is one of the programs organized by the Ministry of Education, Culture, Research and Technology (Kemdikbud). One of the activities in it is the Teaching Campus Program. The purpose of the Teaching Campus Program is to contribute and assist in Teaching, Technology Adaptation, and Administration activities. Currently, the Teaching Campus Program has entered its third year. One of the schools targeted for the Teaching Campus program is SDN 1 Monggas which is located in Monggas Village, Kopang District, Central Lombok Regency. In this program, students from different campuses are placed in the same area and school to assist the school in terms of teaching, adapting technology and administration. In addition, students are also tasked with enforcing independent learning and improving student character and increasing student interest in learning during this pandemic. Another thing that is the goal of this teaching campus program is that students can go directly to the field, add relationships and develop insight and soft skills to participate in improving the quality of education in Indonesia.